SILASE DAUN KETELA KARET TERHADAP DARAH, AMONIA RUMEN, PERTAMBAHAN BOBOT BADAN KAMBING - hanung dhidhik arifin; - - Zulfanita (Surya Agritama : Jurnal Ilmu Pertanian dan Peternakan, 2014)
The research was conducted used 12 of Jawarandu goats which age is 8 mothns and weight of before research is 20 kg. The goats was classified in 4 group and 3 repeat, the heed is 3%body weight (DM) there are silage of cassava leaf and rice bran. Design of research was used Completely Random Design. Treatment of feed are : R0 = 75% cassava leaf + 25%rice bran; R1 = 50% cassava leaf + 25% silage of cassava leaf + 25% rice bran; R2 = 25% cassava leaf + 50% silage of cassava leaf + 25% rice bran; R3 = 75% silage of cassava leaf + 25% rice bran. The variable of research is blood status (erytrocyt, leucocyt, eosinofyl), ammonia of rumen and weight gain. The result of result showed that the silage of cassava leaf improve feed intake of goats but unsignificant, significant to Dry Matter Intake based on weight gain, TDN consumption and Daily weight gain.Silage of cassava leaf is significant to level of rumen ammonia and eritrocyt, but unsignificant to eosinofil of blood.Based on result of research can be conclution that silage and cassava leaf improve feed intake, nutrition intake,rumen condition, blood condition and daily weight gain of Jawarandhu goat. Kata Kunci: Silage, Cassava leaf, Blood, Ammonium of Rumen, Daily Weight Gain